The Assembly Condlitlons Analysis of Planetary Geers with Internal Planet Gear - 吴春英; 周志明; 王信; 梁治国 (Jixie chuandong)
In this paper authors have studied the planetary gears with internal planet gear. The assembly coditions are met by adjusting gear ratio and tooth relative position between internal gear plates. And this paper provides the theory formula for technical application.